Relative Age Effect in Physical Fitness During the Elementary School Years - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Age-groups are commonly implemented in education and sports in order to provide fair and equal opportunities. Various studies, however, have shown a competitive advantage for early born children over their relatively younger peers, which is referred to as relative age effect. The present study examined differences in various components of physical fitness in Austrian elementaryschool children. A total of 18,168 children (51% boys) between 6 and 11 years of age provided valid data on anthropometric characteristics and physical fitness. Specifically, children completed eight fitness tests that assessed cardiorespiratory endurance, muscular strength and power, speed, agility, flexibility and object control. Across age-specific quartiles, older children were significantly taller and heavier than their younger peers. Older children also displayed better performance for strength and power, speed, agility and object control, while differences in cardio-respiratory endurance were less pronounced. These results highlight the presence of a relative age effect during the elementary school years and emphasize the need to consider individual differences in the evaluation of children s performance. As all children should be given equal opportunities to engage successfully in physical education and sports, physical education teachers and youth coaches need to be educated on the implications of a relative age effect. Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.